Two Neglected Insect Enemies of Lac - Mahdihassan, S. (Indian Forester, 1947)
During the monsoon season Sliorea tatum, the bost plant of the Mysore lac insect, suffers from the attack of aphids which invite their own enemies. Of them Chrysopa larvae and Reduviid bugs are equally injurious to lac and must be considered as major, rather than minor, enemies of lac. The kind of injury done by these enemies is shown by photographic illustrations in plate.